Implementation of Educational Puzzle Media with Local Wisdom Nuances: An Analytical Study on Elementary School Students’ Science and Social Learning Outcomes - Anjela Jenista Tuku; Moh. Rudini; Muh. Khaerul Ummah BK (Program Studi PGSD Universitas Madako Tolitoli, 2026)
The low level of students’ learning outcomes, which is presumed to be influenced by the limited use of contextual learning media grounded in local wisdom, has frequently attracted scholarly attention. This study employed a quasi-experimental approach with a non-equivalent control group design, involving 75 fourth-grade students of SDN Pembina Tolitoli. The participants were divided into an experimental group (37 students) and a control group (38 students) using a matching group technique. Data were collected through learning outcome tests (pre-test and post-test) as well as observation sheets, and subsequently analyzed using the Mann–Whitney U test. The findings revealed a significant improvement in the experimental group, with the mean score increasing from 46.96 in the pre-test to 82.35 in the post-test. In contrast, the control group showed an increase from 40.92 to 62.44. Statistically, a significance value of 0.000 (< 0.05) indicates a meaningful difference between the two groups. These results demonstrate that local wisdom-based educational puzzle media is effective in enhancing students’ learning outcomes through active engagement and contextualization of learning materials. The implications of this study highlight the importance of integrating local wisdom into the design of instructional media to improve the quality of learning in elementary education.